Measurements of production cross sections of the Higgs boson in the four-lepton final state in proton–proton collisions at √s=13Te - KAYA, MİTHAT (My University, 2021)
© 2021, CERN for the benefit of the CMS collaboration.Production cross sections of the Higgs boson are measured in the H → Z Z → 4 ℓ (ℓ=e,μ) decay channel. A data sample of proton–proton collisions at a center-of-mass energy of 13Te, collected by the CMS detector at the LHC and corresponding to an integrated luminosity of 137fb-1 is used. The signal strength modifier μ, defined as the ratio of the Higgs boson production rate in the 4 ℓ channel to the standard model (SM) expectation, is measured to be μ=0.94±0.07(stat)-0.08+0.09(syst) at a fixed value of mH=125.38Ge. The signal strength modifiers for the individual Higgs boson production modes are also reported. The inclusive fiducial cross section for the H → 4 ℓ process is measured to be 2.84-0.22+0.23(stat)-0.21+0.26(syst)fb, which is compatible with the SM prediction of 2.84±0.15fb for the same fiducial region. Differential cross sections as a function of the transverse momentum and rapidity of the Higgs boson, the number of associated jets, and the transverse momentum of the leading associated jet are measured. A new set of cross section measurements in mutually exclusive categories targeted to identify production mechanisms and kinematical features of the events is presented. The results are in agreement with the SM predictions.
Keywords: Fizik; Astronomi ve Astrofizik; Temel Bilimler; Mühendislik ve Teknoloji; Physics; Astronomy and Astrophysics; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; Uzay bilimi; ASTRONOMİ VE ASTROFİZİK; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; SPACE SCIENCE; ASTRONOMY & ASTROPHYSICS; Mühendislik (çeşitli); Fizik Bilimleri; Fizik ve Astronomi (çeşitli); Engineering (miscellaneous); Physical Sciences; Physics and Astronomy (miscellaneous)